A Comprehensive Study On The Pre-Fabricated Modular House - Wee, Farrah Yee Zhen (2022)
In the construction industry, the anticipation of effectiveness and sustainability exists within every construction project. A proper construction method has to be adopted to obtain the desired outcomes. However, due to the uncommonness of modular buildings in Malaysia and only being at the early implementation stage of modular construction, the numerous advantages that can be provided have been squandered. This study aims to establish an innovative conceptual design for a modular house and analyse its feasibility. A thorough literature review was carried out to conduct the research, and the modular house conceptual design was proposed using SketchUp software. The feasibility study of the modular house was performed by evaluating it from different aspects and by performing a SWOT analysis. The modular house proposed is an 1800 square feet single-storey residential house with a timber frame, and it consists of three bedrooms, two bathrooms, an open plan kitchen, and a living room. It exudes an aesthetic and modern ambience and is best suited for a family to reside. After performing the SWOT analysis and evaluating the modular house that has been proposed, it can be said that the conceptual design is feasible. Nonetheless, proper planning must be ensured for the project to successfully undergo. On the whole, modular construction is a promising method that should be widely adopted by the key players in the construction industry to make the best out of it and to become more innovative in the future.